Pajak Konten Creator: Analisis Komparatif Sistem Self-Assessment Indonesia dan Mandatory Platform Reporting Australia - Reinhart, Frederick; Lewiandy, Lewiandy (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The rapid digitalization of the global economy has transformed income generation, giving rise to content creators as key actors in the creative sector. In Indonesia, tax administration for content creators remains problematic under the self-assessment system, which relies on voluntary compliance. Structural weaknesses such as limited taxpayer understanding, administrative inefficiency, and the absence of third-party data verification have resulted in low compliance and potential tax leakage, especially from cross-border digital income. In contrast, Australia’s Mandatory Platform Reporting or Sharing Economy Reporting Regime (SERR) introduces a data-driven model by requiring digital platforms to report users’ income directly to the Australian Taxation Office (ATO). This normative legal research conducts a comparative analysis of both systems, identifying the deficiencies in Indonesia’s self-assessment model and evaluating the effectiveness of SERR as a model for reform. The study concludes that Indonesia can enhance transparency, fairness, and tax compliance through legal reform, platform accountability, and data integration, transitioning from voluntary disclosure to data-based compliance.